2022
DOI: 10.1002/pan3.10330
|View full text |Cite
|
Sign up to set email alerts
|

Species diversity enhances perceptions of urban coastlines at multiple scales

Abstract: 1. Biodiversity is increasingly understood as an important mediator of human aesthetic appreciation of scenes and landscapes, with implications for cultural services and well-being. However, the generality of biodiversity effects across affective emotions, scales and habitats remains unclear.2. Urban coastal intertidal habitats on seawalls and other artificial structures are expanding worldwide. Despite growing calls to prioritise biodiversity in urban coastal planning and management, the potential co-benefits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 155 publications
0
5
0
Order By: Relevance
“…The prioritisation of environmental over societal (socio-economic) benefits, irrespective of an individual's background or research interest, is becoming more commonplace as the value of the environment to human health and well-being is increasingly recognised (Soga and Gaston, 2020). Recent studies assessing perceptions of coastal defence structures show that stakeholders prioritise ecological features or benefits over socio-economic or technical aspects of that infrastructure (Evans et al, 2017;Fairchild et al, 2022), despite environmental benefits often being intangible to many (sensu Lim et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The prioritisation of environmental over societal (socio-economic) benefits, irrespective of an individual's background or research interest, is becoming more commonplace as the value of the environment to human health and well-being is increasingly recognised (Soga and Gaston, 2020). Recent studies assessing perceptions of coastal defence structures show that stakeholders prioritise ecological features or benefits over socio-economic or technical aspects of that infrastructure (Evans et al, 2017;Fairchild et al, 2022), despite environmental benefits often being intangible to many (sensu Lim et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, however, the economic valuation of ecosystem services associated with GGI is in its infancy (e.g. Mehvar et al, 2018), but is nonetheless essential to support or challenge economic justifications by enabling cost-benefit analysis (Fairchild et al, 2022). Economic values include societal benefits via greater knowledge gained of GGI (Strain et al 2019), a perceived increase in naturalness and biodiversity, as well as an association with healthy environments (Fairchild et al, 2021;SalaĂŒn et al, 2022).…”
Section: Greater Consideration For Ecosystem Servicesmentioning
confidence: 99%
“…-Considering socio-economic benefits Evans et al, 2017;Kienker et al, 2018;Evans et al, 2019;Morris et al, 2019;Strain et al, 2019;Sawyer et al, 2020;Fairchild et al, 2022;Accola et al, 2022a,b;SalaĂŒn et al, 2022;Aguilera et al, 2023b). -Consideration of other metrics such as trophic structure (Espinosa et al, 2020;Sedano et al, 2020a,b;Raoux et al, 2022), sedimentation (Bone et al, 2022b;Martinez et al, 2022), transport of wrack (Strain et al, 2018b;Critchley et al, 2021), litter accumulation (Aguilera et al, 2016(Aguilera et al, , 2018(Aguilera et al, , 2023a, use by terrestrial predators or pest species (Aguilera et al, 2023a), early life stage usage (Mafanya, 2020;Reddy, 2022).…”
Section: Greening Of Grey Infrastructure (Ggi) On Marine Artificial S...mentioning
confidence: 99%
“…While ecologically beneficial solutions were favoured most, opportunities for enhancing the sociocultural value of coastal structures were also mentioned (Evans et al, 2017). Moreover, a study by Fairchild et al (2022) on the public perception of biodiversity on coastal structures found that increased complexity positively affects perception at a range of structural scales, suggesting that ecological enhancements in multi-purpose coastal engineering solutions themselves already increase sociocultural value.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Moreover, a study by Fairchild et al. (2022) on the public perception of biodiversity on coastal structures found that increased complexity positively affects perception at a range of structural scales, suggesting that ecological enhancements in multi‐purpose coastal engineering solutions themselves already increase sociocultural value.…”
Section: Introductionmentioning
confidence: 99%